2019
DOI: 10.3390/nu11051064
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of a Collagen Hydrolysate Enhances Postprandial Absorption Rate—A Randomized Controlled Trial

Abstract: Collagen is characterized by its high content of glycine, proline and hydroxyproline, and is found to exert beneficial effects on joint pain related to activity and osteoarthritis. However, to exert any beneficial effects it is essential that collagen is optimally absorbed. This study aimed to investigate the postprandial absorption of collagen and elucidate the impact of an exogenous enzymatic hydrolysis on absorption rate and bioavailability. A randomized, blinded, cross-over study was conducted where ten he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
2
49
2
Order By: Relevance
“…This is to be expected given the slightly higher dose within our current protocol. However, others have shown similar plasma values after the ingestion of 35 g of collagenous protein (32) which they suggest shows an upper threshold to the AA availability of collagen proteins. In general since all AAs appeared to peak between 30 and 60 min (Table 2), the consumption of ~ 20 g of protein within the 30–60 min prior to exercise would ensure the optimal availability of AAs at a time when synthetic machinery is upregulated, and tissue perfusion supported (13, 46, 49).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is to be expected given the slightly higher dose within our current protocol. However, others have shown similar plasma values after the ingestion of 35 g of collagenous protein (32) which they suggest shows an upper threshold to the AA availability of collagen proteins. In general since all AAs appeared to peak between 30 and 60 min (Table 2), the consumption of ~ 20 g of protein within the 30–60 min prior to exercise would ensure the optimal availability of AAs at a time when synthetic machinery is upregulated, and tissue perfusion supported (13, 46, 49).…”
Section: Discussionmentioning
confidence: 82%
“…It has been suggested that hydrolysis of collagen protein prior to ingestion allows two and three amino acid peptides to pass across the mucosal barrier equating to a higher expression and therefore biosynthesis within the tissue matrix (31). This was illustrated in a recent study whereby the consumption of hydrolysed collagen proteins resulted in a higher bioavailability of AAs compared to non-hydrolysed collagen protein and a placebo control (32). Furthermore, it has recently been shown that the consumption of collagen peptides resulted in a higher expression of collagen signaling proteins, compared to a placebo control (24).…”
Section: Introductionmentioning
confidence: 98%
“…For instance, proteins that contain greater amounts of glycine and proline may deliver more amino acid precursors required to support higher postexercise intramuscular connective tissue protein synthesis rates. Dietary collagen protein sources, such as collagen hydrolysate and gelatin, have been reported to contain approximately 26% and 12% of glycine and proline, respectively ( 40 ). Recent work by Shaw et al ( 41 ) demonstrates that 15 g gelatin ingestion robustly increases plasma glycine and proline concentrations, leading to greater collagen synthesis rates in tissue constructs in an ex vivo setting.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of fermented beverages containing milk whey has the disadvantage of low solids and casein content, giving a watery consistency to the final products. However, the addition of fresh milk, condensed milk, milk powder, or some other additives to improve the textural and nutritional characteristics of the final products is common [ 15 ]. The first step to obtain hydrolyzed collagen (HC) is the denaturation of the native collagen identified for the separation of 3 α-chains.…”
Section: Introductionmentioning
confidence: 99%